Dihydropyrimidinase deficiency with atrioventricular septal defect: a case report - Erdal, Izzet; Yıldız, Yılmaz; Kuseyri Hübschmann, Oya; Haas, Dorothea; Günbey, Ceren; Ertuğrul, İlker; Yalnızoğlu, Dilek (The journal of pediatric endocrinology and metabolism, 2024)
Objectives Dihydropyrimidinase deficiency is a rare autosomal recessive disorder of the pyrimidine degradation pathway, with fewer than 40 patients published. Clinical findings are variable and some patients may remain asymptomatic. Global developmental delay and increased susceptibility to 5-fluorouracil are commonly reported. Here we present atrioventricular septal defect as a novel feature in dihydropyrimidinase deficiency. Case presentation A four-year-old male with global developmental delay, dysmorphic facies, autistic features and a history of seizures was diagnosed with dihydropyrimidinase deficiency based on strikingly elevated urinary dihydrouracil and dihydrothymine and a homozygous pathogenic nonsense variant in DPYS gene. He had a history of complete atrioventricular septal defect corrected surgically in infancy. Conclusions This is the second report of congenital heart disease in dihydropyrimidinase deficiency, following a single patient with a ventricular septal defect. The rarity of the disease and the variability of the reported findings make it difficult to describe a disease-specific clinical phenotype. The mechanism of neurological and other systemic findings is unclear. Dihydropyrimidinase deficiency should be considered in patients with microcephaly, developmental delay, epilepsy and autistic traits. We suggest that congenital heart disease may also be a rare phenotypic feature.